1987
DOI: 10.1002/app.1987.070330604
|View full text |Cite
|
Sign up to set email alerts
|

Low‐angle laser light scattering–aqueous size exclusion chromatography of polysaccharides: Molecular weight distribution and polymer branching determination

Abstract: SynopsisA low-angle laser light scattering detector (LALLS) used with size exclusion chromatography (SEC/LALLS) has been applied for the determination of molecular weight, molecular weight distribution (MWD), and degree of branching of polysaccharides in 0.5N NaOH aqueous solution. Data from both detectors [differential refractive index (DRI) and LALLS] are used to calculate the absolute molecular weight at each point in a sample chromatogram. The correct average molecular weight and MWD can be obtained withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…The collected data from MALS and RI detectors were analyzed using a Berry plot for curve fitting with Astra software version V (Wyatt Tech. Corp., Santa Barbara, CA), and a dn/dc value of 0.146 mL/g was applied for M w calculation [32], [33].…”
Section: Methodsmentioning
confidence: 99%
“…The collected data from MALS and RI detectors were analyzed using a Berry plot for curve fitting with Astra software version V (Wyatt Tech. Corp., Santa Barbara, CA), and a dn/dc value of 0.146 mL/g was applied for M w calculation [32], [33].…”
Section: Methodsmentioning
confidence: 99%
“…In both cases, samples of the fermentation broth were taken at 12 hour intervals and centrifuged to remove the bacterial cells (10,000 RPMs for 30 minutes), decanted, and analyzed by SEC/LALLS. The specific details of the SEC/LALLS apparatus are described elsewhere (Yu and Rollings, 1987).…”
Section: Gethods and Uaterialsmentioning
confidence: 99%
“…The utility of SEC/LALLS for polysaccharide characterization (Yu and Rollings, 1987;Yu and Rollings, 1988;Cael et al, 1983) has been previously demonstrated. Size exclusion chromatography separates molecules based on their hydrodynamic size in dilute solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Size exclusion chromatography (SEC) has been used extensively for characterization of carbohydrate polymers, including capsular bacterial polysaccharides (and their conjugates) that are used as important vaccine products to ensure both the stability and effective immunogenicity (Gaborieau & Castignolles, 2011;Lee et al, 2009;Mori & Barth, 2013;Pato, Antonio de Pádua & da Silva Junior, 2006;von Hunolstein, Parisi & Bottaro, 2003;Yu & Rollings, 1987). For example, Lee et al (2009) used size exclusion chromatography for the purification and analysis of a meningococcal conjugated vaccine.…”
mentioning
confidence: 99%